The Change Created By Syrian Asylum Seekers in Health and Nursing Services Provided in Hospitals: A Qualitative Study - Ayşe Çiçek Korkmaz; Ülkü Baykal (Nursing and Health Sciences Journal (NHSJ), 2023)
This study aims at determining the change created by Syrian asylum seekers, who came to Turkey due to the Syrian war, in the health and nursing services provided in hospitals located in Turkey’s border region. This qualitative research was conducted with 68 nurses who provided treatment and care services for Syrian asylum seekers during intense periods of the Syrian war. Data was collected with the semi-structured in-depth individual interview form and the content analysis method. Seven subthemes were determined under two main themes: Physical structure, hospital equipment, and the change caused by the general health services offered by the hospital are the subthemes under the main theme ‘change in healthcare’; and the inability to nursing process, lack of resources, failure to ensure patient safety, failure to ensure employee safety, and problems regarding working conditions are the subthemes under the main theme ‘change in nursing services’. Since this is the first study on this subject in Turkey, there is a need for more comprehensive studies on the subject that examine different professional groups. The numbers of asylum seekers throughout the world is increasing every day. Therefore, determining how asylum seekers have made a change in health and nursing services may be useful in terms of the possible measures and improvements to be taken in migration situations.